Coordinated hydrological regimes in the Indo-Pacific region during the past two millennia - Tierney, J. E.; Oppo, D. W.; Rosenthal, Y.; Russell, J. M.; Linsley, B. K. (Paleoceanography, 2010)
Instrumental data suggest that major shifts in tropical Pacific atmospheric dynamics and hydrology have occurred within the past century, potentially in response to anthropogenic warming. To better understand these trends, we use the hydrogen isotopic ratios of terrestrial higher plant leaf waxes ( delta D-wax) in marine sediments from southwest Sulawesi, Indonesia, to compile a detailed reconstruction of central Indo-Pacific Warm Pool (IPWP) hydrologic variability spanning most of the last two millennia. Our paleodata are highly correlated with a monsoon reconstruction from Southeast Asia, indicating that intervals of strong East Asian summer monsoon (EASM) activity are associated with a weaker Indonesian monsoon (IM). Furthermore, the centennial-scale oscillations in our data follow known changes in Northern Hemisphere climate ( e. g., the Little Ice Age and Medieval Warm Period) implying a dynamic link between Northern Hemisphere temperatures and IPWP hydrology. The inverse relationship between the EASM and IM suggests that migrations of the Intertropical Convergence Zone and associated changes in monsoon strength caused synoptic hydrologic shifts in the IPWP throughout most of the past two millennia.
id: 795; 565UW Times Cited:0 Cited References Count:42Y

Reduced North Atlantic Central Water formation in response to early Holocene ice-sheet melting - Bamberg, A.; Rosenthal, Y.; Paul, A.; Heslop, D.; Mulitza, S.; Ruhlemann, C.; Schulz, M. (Geophysical Research Letters, 2010)
Central waters of the North Atlantic are fundamental for ventilation of the upper ocean and are also linked to the strength of the Atlantic Meridional Overturning Circulation (AMOC). Here, we show based on benthic foraminiferal Mg/Ca ratios, that during times of enhanced melting from the Laurentide Ice Sheet (LIS) between 9.0-8.5 thousand years before present (ka) the production of central waters weakened the upper AMOC resulting in a cooling over the Northern Hemisphere. Centered at 8.54 +/- 0.2 ka and 8.24 +/- 0.1 ka our dataset records two similar to 150-year cooling events in response to the drainage of Lake Agassiz/Ojibway, indicating early slow-down of the upper AMOC in response to the initial freshwater flux into the subpolar gyre (SPG) followed by a more severe weakening of both the upper and lower branches of the AMOC at 8.2 ka. These results highlight the sensitivity of regional North Atlantic climate change to the strength of central-water overturning and exemplify the impact of both gradual and abrupt freshwater fluxes on eastern SPG surface water convection. In light of the possible future increase in Greenland Ice Sheet melting due to global warming these findings may help us to better constrain and possibly predict future North Atlantic climate change. Citation: Bamberg, A., Y. Rosenthal, A. Paul, D. Heslop, S. Mulitza, C. Ruhlemann, and M. Schulz (2010), Reduced North Atlantic Central Water formation in response to early Holocene ice-sheet melting, Geophys. Res. Lett., 37, L17705, doi: 10.1029/2010GL043878.
id: 874; 649FZ Times Cited:3 Cited References Count:32submittedY

2,000-year-long temperature and hydrology reconstructions from the Indo-Pacific warm pool - Oppo, D. W.; Rosenthal, Y.; Linsley, B. K. (Nature, 2009)
Northern Hemisphere surface temperature reconstructions suggest that the late twentieth century was warmer than any other time during the past 500 years and possibly any time during the past 1,300 years (refs 1, 2). These temperature reconstructions are based largely on terrestrial records from extra-tropical or high-elevation sites; however, global average surface temperature changes closely follow those of the global tropics(3), which are 75% ocean. In particular, the tropical Indo-Pacific warm pool (IPWP) represents a major heat reservoir that both influences global atmospheric circulation(4) and responds to remote northern high-latitude forcings(5,6). Here we present a decadally resolved continuous sea surface temperature (SST) reconstruction from the IPWP that spans the past two millennia and overlaps the instrumental record, enabling both a direct comparison of proxy data to the instrumental record and an evaluation of past changes in the context of twentieth century trends. Our record from the Makassar Strait, Indonesia, exhibits trends that are similar to a recent Northern Hemisphere temperature reconstruction(2). Reconstructed SST was, however, within error of modern values from about AD 1000 to AD 1250, towards the end of the Medieval Warm Period. SSTs during the Little Ice Age ( approximately AD 1550-1850) were variable, and similar to 0.5 to 1 degrees C colder than modern values during the coldest intervals. A companion reconstruction of delta O-18 of sea water-a sea surface salinity and hydrology indicator-indicates a tight coupling with the East Asian monsoon system and remote control of IPWP hydrology on centennial-millennial timescales, rather than a dominant influence from local SST variation.
id: 860; ISI Document Delivery No.: 487YE Times Cited: 2 Cited Reference Count: 29 Cited References: *INT AT ENAG WORLD, 2006, GNIP PROGR RES *NAT RES COUNC, 2006, SURF TEMP REC LAST 2 ALDRIAN E, 2003, INT J CLIMATOL, V23, P1435, DOI 10.1002/joc.950 ANAND P, 2003, PALEOCEANOGRAPHY, V18, ARTN 1050 BARSUGLI JJ, 2002, J CLIMATE, V15, P3427 BROCCOLI AJ, 2006, GEOPHYS RES LETT, V33, ARTN L01702 CHIANG JCH, 2005, CLIM DYNAM, V25, P477, DOI 10.1007/s00382-005-0040-5 CONROY JL, 2008, QUATERNARY SCI REV, V27, P1166, DOI 10.1016/j.quascirev.2008.02.015 GORDON AL, 2003, NATURE, V425, P824, DOI 10.1038/nature02038 HAUG GH, 2001, SCIENCE, V293, P1304 JANSEN E, 2007, CLIMATE CHANGE 2007, P466 KAWAHATA H, 2002, DEEP-SEA RES PT II, V49, P2783 LEA DW, 2000, SCIENCE, V289, P1719 LOCARNINI RA, 2006, NOAA ATLAS NESDIS, V61 MANN ME, 2008, P NATL ACAD SCI USA, V105, P13252, DOI 10.1073/pnas.0805721105 MOHTADI M, 2009, PALEOCEANOGRAPHY, V24, ARTN PA1201 MOY CM, 2002, NATURE, V420, P162 NEWTON A, 2006, GEOPHYS RES LETT, V33, ARTN L19710 QU T, 2005, OCEANOGRAPHY, V18, P50 ROSENTHAL Y, 2003, GEOPHYS RES LETT, V30, DOI 10.1029/2002GL016612 SMITH TM, 2008, J CLIMATE, V21, P2283, DOI 10.1175/2007JCLI2100.1 SONTAKKE NA, 1993, J CLIMATE, V6, P1807 STOTT L, 2004, NATURE, V431, P56, DOI 10.1038/nature02903 THUNELL RC, 1984, MICROPALEONTOLOGY, V30, P243 VUILLE M, 2005, J GEOPHYS RES-ATMOS, V110, ARTN D23108 WANG YJ, 2005, SCIENCE, V308, P854, DOI 10.1126/science.1106296 XIE PP, 1996, J CLIMATE, V9, P840 YANCHEVA G, 2007, NATURE, V445, P74, DOI 10.1038/nature05431 ZHANG PZ, 2008, SCIENCE, V322, P940, DOI 10.1126/science.1163965 Oppo, Delia W. Rosenthal, Yair Linsley, Braddock K.; YY

3500 yr record of centennial-scale climate variability from the Western Pacific Warm Pool - Langton, S. J.; Linsley, B. K.; Robinson, R. S.; Rosenthal, Y.; Oppo, D. W.; Eglinton, T. I.; Howe, S. S.; Djajadihardja, Y. S.; Syamsudin, F. (Geology, 2008)
We use geochemical data from a sediment core in the shallow-silled and intermittently dysoxic Kau Bay in Halmahera (Indonesia, lat 1 degrees N, long 127.5 degrees E) to reconstruct century-scale climate variability within the Western Pacific Warm Pool over the past similar to 3500 yr. Downcore variations in bulk sedimentary delta N-15 appear to reflect century-scale variability in basin ventilation, attributed to changes in oceanographic conditions related to century-scale fluctuations in El Nino Southern Oscillation (ENSO). We infer an increase in century-scale El Nino activity beginning ca. 1700 yr B.P. with peaks in El Nino activity ca. 1500 yr B.P., 1150 yr B.P., and ca. 700 yr B.P. The Kau Bay results suggest that there was diminished ENSO amplitude or frequency, or a departure from El Nino-like conditions during the Medieval Warm Period, and distinctive, but steadily decreasing, El Nino activity during and after the Little Ice Age.
id: 1894; ISI Document Delivery No.: 357HB Times Cited: 1 Cited Reference Count: 36 Cited References: ALDRIAN E, 2003, INT J CLIMATOL, V23, P1435, DOI 10.1002/joc.950 ALTABET MA, 1994, GLOBAL BIOGEOCHEM CY, V8, P103 ALTABET MA, 2001, LIMNOL OCEANOGR, V46, P368 ARRUDA WZ, 2003, J PHYS OCEANOGR, V33, P2815 BRANDES JA, 1998, LIMNOL OCEANOGR, V43, P1680 BRANDES JA, 2002, GLOBAL BIOGEOCHEMICA, V16 CASCIOTTI KL, 2002, ANAL CHEM, V74, P4905, DOI 10.1021/ac020113w CHRISTIAN JR, 2004, DEEP-SEA RES PT II, V51, P209, DOI 10.1016/j.dsr2.2003.06.002 DEUTSCH C, 2007, NATURE, V445, P163, DOI 10.1038/nature05392 GANESHRAM RS, 2000, PALEOCEANOGRAPHY, V15, P361 GRANGER J, 2004, EOS T AM GEOPHYS U S, V85 GRANGER J, 2004, LIMNOL OCEANOGR, V49, P1763 HAUG GH, 1998, PALEOCEANOGRAPHY, V13, P427 HAUG GH, 2001, SCIENCE, V293, P1304 HODELL DA, 2005, QUATERNARY SCI REV, V24, P1413, DOI 10.1016/j.quascirev.2004.10.013 LIU KK, 1989, LIMNOL OCEANOGR, V34, P820 MAKOU MC, 2007, ORG GEOCHEM, V38, P1680, DOI 10.1016/j.orggeochem.2007.06.003 MARIOTTI A, 1981, PLANT SOIL, V62, P413 MASUMOTO Y, 2001, GEOPHYS RES LETT, V28, P1631 MIDDELBURG JJ, 1990, GEOL ULTRIECTIN, V71, P177 MOY CM, 2002, NATURE, V420, P162 NEWTON A, 2006, GEOPHYS RES LETT, V33, ARTN L19710 REIN B, 2004, GEOPHYS RES LETT, V31, ARTN L17211 REIN B, 2005, PALEOCEANOGRAPHY, V20, ARTN PA4003 REYNOLDS RW, 1994, J CLIMATE, V7, P929 RODBELL DT, 1999, SCIENCE, V283, P516 SIGMAN DM, 2003, GEOCHEM GEOPHY GEOSY, V4, ARTN 1040 SIGMAN DM, 2005, GLOBAL BIOGEOCHEM CY, V19, ARTN GB4022 STOTT L, 2004, NATURE, V431, P56, DOI 10.1038/nature02903 STREETPERROTT FA, 1997, SCIENCE, V278, P1422 THUNELL R, 2004, GLOBAL BIOGEOCHEMICA, V18, UNSP GB3001 UEKI I, 2003, J GEOPHYS RES-OCEANS, V108, ARTN 3243 VANAKEN HMV, 1988, NETHERLANDS J SEA RE, V22, P403, DOI 10.1016/0077-7579(88)90011-7 VANDERWEIJDEN CH, 1989, NETH J SEA RES, V24, P583 VANRIEL PM, 1943, OCEANOGRAPHIC RESU 5, V2 WYRTKI K, 1961, NAGA REPORT, V2 Langton, S. J. Linsley, B. K. Robinson, R. S. Rosenthal, Y. Oppo, D. W. Eglinton, T. I. Howe, S. S. Djajadihardja, Y. S. Syamsudin, F. U.S. National Science Foundation [OCE-0502550, OCE-0502504, OCE-052960] This work was supported by the U.S. National Science Foundation (grants OCE-0502550, OCE-0502504, and OCE-052960). We thank the captain, crew, technicians, and the scientific crew who helped with sample collection on the R/V Baruna Jaya VIII. Geological soc amer, inc Boulder; YY

The 8200 year B. P. event in the slop water system, western sublpolar North Atlantic - Keigwin, L. D.; Sachs, J. P.; Rosenthal, Y.; Boyle, E. A. (Paleoceanography, 2005)
id: 1097

A 1600-year history of the Labrador Current off Nova Scotia - Keigwin, L. D.; Sachs, J. P.; Rosenthal, Y. (Climate Dynamics, 2003)
A multicore from Emerald Basin, on the continental margin off Nova Scotia, has a modern C-14 age at the top, and other C-14 dates indicate a linear sedimentation rate of similar to30 cm/ka to 1600 calendar years BP. This rate is great enough to record century-to-millennial scale changes in the surface and deep (similar to250 m) waters in the basin that are influenced by the Labrador Current. We applied five proxies for seawater temperature changes to the sediments of Emerald Basin, including the percent abundance and the oxygen isotope ratio (delta(18)O) of the polar planktonic foraminifer N. pachyderma (s.), the unsaturation ratio of alkenones (U-37(k')) produced by prymnesiophyte phytoplankton, and the delta(18)O and Mg/Ca of benthic foraminifera. All five proxies indicate the ocean warmed suddenly sometime in the past 150 years or so. The exact timing of this event is uncertain because C-14 dating is inaccurate in recent centuries, but this abrupt warming probably correlates with widespread evidence for warming in the Arctic in the nineteenth century. Because the Canadian Archipelago is one of the two main sources for the Labrador Current, warming and melting of ice caps in that region may have affected Labrador Current properties. Before this recent warming, sea surface temperature was continually lower by 1-2 degreesC, and bottom water was colder by about 6 degreesC in Emerald Basin. These results suggest that there was no Medieval Warm Period in the coastal waters off Nova Scotia. Because there is also no evidence of medieval warming in the Canadian archipelago, it seems likely that coastal waters from Baffin Bay to at least as far south as Nova Scotia were continually cold for similar to1500 of the past 1600 years.
698thTimes Cited:25Cited References Count:31

The amplitude and phasing of climate change during the last deglaciation in the Sulu Sea, western equatorial Pacific - Rosenthal, Y.; Oppo, D. W.; Linsley, B. K. (Geophysical Research Letters, 2003)
[1] Variations in tropical sea surface temperature patterns and the phasing relative to climate change in higher-latitudes provide insight into the mechanisms of climate change on both orbital and shorter time-scales. Here, we present well-dated, high-resolution records of planktonic foraminiferal delta(18)O and Mg/Ca-based SST spanning the last deglaciation from the Sulu Sea, located in the western equatorial Pacific. The results indicate that the last glacial maximum was 2.3 +/- 0.5degreesC cooler than present in the Sulu Sea with a concomitant decrease in sea surface salinity. The similarity between variations in surface salinity in the Sulu Sea, the western and eastern equatorial Pacific, and the Greenland ice-core record suggests that the observed changes in salinity reflect large-scale rearrangement of atmospheric patterns, which were coherent and synchronous throughout the Northern Hemisphere. The results suggest that the glacial equatorial Pacific climate was strongly influenced by both tropical, and extra-tropical forcing, although it is not clear whether interannual (ENSO) variability is a good analogue of glacial-interglacial climate change.
677zxTimes Cited:122 Cited References Count:18
Keywords: china; enso; level; monsoon; record; surface temperature

East Asian monsoon forcing of suborbital variability in the Sulu Sea during Marine Isotope Stage 3: Link to Northern Hemisphere climate - Dannenmann, S.; Linsley, B. K.; Oppo, D. W.; Rosenthal, Y.; Beaufort, L. (Geochemistry Geophysics Geosystems, 2003)
[1] We have generated a new high-resolution record of variations in planktonic foraminiferal oxygen isotopes (delta(18)O) and Mg/Ca from a sediment core (IMAGES 97-2141) in the Sulu Sea located in the Philippine archipelago of western tropical Pacific. This record reveals distinct, suborbital-scale delta(18)O changes, most notably during Marine Isotope Stage 3 (MIS3) (similar to30,000 to 60,000 years B.P.). The amplitudes of these delta(18)O fluctuations (0.4 to 0.7parts per thousand) exceed that which can be attributed to sea level changes and must be due to changes in sea surface conditions. In the same interval, variations in planktonic foraminifera Mg/Ca suggest that suborbital surface ocean temperature variations of 1 to 1.5degreesC in the Sulu Sea were not in phase with delta(18)O. Combined, this evidence indicates that the MIS3 millennial delta(18)O events in the Sulu Sea were primarily the result of changes in surface water salinity, which today is directly related to the East Asian Monsoon (EAM) and its influence on the balance between surface water contributions from the South China Sea and Western Pacific Warm Pool (WPWP). Within dating uncertainties the MIS3 Sulu Sea delta(18)O suborbital variability indicates that times of fresher surface conditions in the Sulu Sea coincide with similar conditions in the WPWP [Stott et al., 2002] and also with intensifications of the summer EAM as recorded in the U-Th dated Chinese (Hulu Cave) speleothem delta(18)O record [Wang et al., 2001] and thus by inference with interstadials in the Greenland Ice core records. Combined, these results indicate that pronounced suborbital variability in the summer EAM and Intertropical Convergence Zone (ITCZ) during MIS3 was tightly coupled with climate conditions in the northern high latitudes.
631mwTimes Cited:41 Cited References Count:53
Keywords: 1620 global change : climate dynamics (3309); 4267 oceanography : general : paleoceanography; dissolution; equatorial pacific; eurasian snow cover; isotope stage 3; last glacial period; late pleistocene; Mg/Ca; millennial-scale climate change; oxygen isotopes; paleoceanography; planktonic-foraminifera; records; se asian monsoon; south china sea; summer monsoon; surface temperature-variations